Solar Ponds as Heat Source for Low-Temperature Multi-effect Distillation Plants* - Tabor, H (Annals of Arid Zone, 2016)
Non-convecting solar ponds have the potential of providing low-temperature heat well below current fuel prices. The development of multi-effect distillation plants operating below 100Â°C allows solar ponds to be considered as the heat source. The paper discusses optimization of the size of the pond and the number of effects used, taking into account the large variation of pond heat output between summer and winter. One result is that, for current cost data it pays to oversize the pond - leading to some rejection of heat in the summer (which is referred to as peak clipping) - because this leads to a better utilization of the desalination plant and a reduction in the summer-winter yield ratio. For Israel conditions, the peak clipping reduces the summer-winter output ratio from 4:1 to approximately 2:1 with the summer output maintained for 200-230 days in the year. Taking the pond cost at an upper figure of 7x 101 per km2, and using costs for a locally produced desalination plant, the system competes with fuel at 42 a , ton or reduces the cost of desalinated water by 18 cents perm3 when compared with a fuel system using fuel at 80 a ton.